Implementation of Contextual Learning Approach in Strengthening Character Education in Elementary Schools - Khairani, Nazla (International Journal of Students Education, 2024)
In the learning process in the classroom, many students have not been able to relate the material they are learning to its application in everyday life. Therefore, a learning method is needed that emphasizes student involvement in finding and connecting material with real situations around them. This study aims to explore the application of a contextual learning approach in strengthening character education for students in elementary schools. The method used in this study is a literature study, by collecting secondary data from various reading sources. The results of the study show that the contextual learning approach has a positive impact on strengthening the character of students at the elementary school level. This approach helps students to relate the material they are learning to its application in everyday life. In addition, the use of a contextual learning approach also supports the achievement of the "Independent Learning" program carried out by the Ministry of Education and Culture (Kemendikbud). This approach plays an important role in realizing learning independence that is in line with the objectives of developing the program.